Asymmetric Palladium‐Catalyzed Alkene Carboamination Reactions for the Synthesis of Cyclic Sulfamides. Issue 17 (10th March 2016) - Garlets, Zachary J.; Parenti, Kaia R.; Wolfe, John P.
Abstract: The synthesis of cyclic sulfamides by enantioselective Pd‐catalyzed alkene carboamination reactions between N ‐allylsulfamides and aryl or alkenyl bromides is described. High levels of asymmetric induction (up to 95:5 e.r.) are achieved using a catalyst composed of [Pd2 (dba)3 ] and ( S )‐Siphos‐PE. Deuterium‐labelling studies indicate the reactions proceed through syn ‐aminopalladation of the alkene and suggest that the control of syn ‐ versus anti ‐aminopalladation pathways is important for asymmetric induction. Abstract : Aminate the double bond ! The enantioselective Pd‐catalyzed coupling of aryl or alkenyl bromides with N ‐allylsulfamides affords substituted cyclic sulfamides in good yield with high levels of asymmetric induction (see scheme). The reactions proceed through stereoselective syn ‐aminopalladation of the alkene, which is important for high enantioselectivity.